Millennium budget: agriculture and rural development - Gulati, Ashok (2000)
The overall approach of the budget in regard to agriculture and rural development, of containing subsidies and increasing investment, is right. But real rationalisation of subsidies requires not merely price revisions but substantial institutional reforms. Similarly, it would require massive doses of investment in irrigation and R and D before a significant weather-proofing of Indian agriculture can be achieved and to expect that the proposals contained in the budget for 2000-2001 can put agriculture on a sustainable growth path of 4 per cent per annum is naive. - Reproduced
Keywords: Agriculture - India; Rural development - India; Budget - India; Budget